Comparison of Density Tests for Thin Hot-Mix Asphalt Overlays. Issue 1 (January 2015) - Wilson, Bryan T.; Sebesta, Stephen
The thin overlay mix (TOM) and ultrathin overlay mix (UTOM) specifications in Texas test falling head water flow as a surrogate measure of density. Current flow time criterion has never been correlated to density; furthermore, there is no maximum flow time to prevent overcompaction. A rolling density meter (radar) and a circular track meter may also be used to measure thin lift density. These tests and traditional core testing were used on three projects, and the correlations between tests were analyzed. Correlations were strong on a project-by-project basis but generally poor when data sets were combined. Flow time and mean profile depth, flow time and core voids, and surface dielectric and core voids were the strongest correlations overall; measured voids were unusually high. The reliability of taking core measurements on such thin samples is questionable and may be overly influenced by the surface texture. The flow test should continue to be used as a surrogate measure of density. No minimum flow time was recommended because of unusually high void measurements. To avoid overcompaction in TOMs, flow time should be less than 6 min on higher-speed or critical sections and less than 10 min on lower-speed, noncritical sections. From the standpoint of macrotexture in the UTOM, no upper limit is recommended for flow time. The rolling density meter should be employed on project-specific issues when full-coverage density measurements are desired. Further testing should be conducted on the reliability of measuring voids on very thin cores.